Simulation-based education for selected communication skills: exploring the perception of post-graduate dental students - Mascarenhas, Sharon (Korean J Med Educ, 2021)
PURPOSE: The role of simulation-based education (SBE) in enhancing communication has been established in the literature. To ensure achieving desired outcomes from SBE initiative, the individual learners, their experiences, and environments need to be considered. This study aimed at exploring the perception of post-graduate dental students regarding their participation in SBE sessions, around selected communication skills, designed in alignment with the assumptions of adult learning theory and steps of Kolb’s experiential learning cycle. METHODS: This study utilized a qualitative design. Six focus-group sessions were conducted following the SBE sessions. The generated data was inductively investigated using a multi-staged participant-focused approach to thematic analysis, based upon constructivist epistemology. NVivo was utilized to facilitate text Fragments’ coding and categorization. RESULTS: Forty-three post-graduate dental students participated. The analysis resulted in 16 categories spread across five sequential phases of the SBE experience. The “input” theme referred to the resources needed for the SBE process, and included three categories: facilities, personnel, and teaching materials. The second theme included steps of SBE “process”: pre-brief, simulation, and debrief. The third, fourth, and fifth themes constituted the short- and longer-term results of the SBE intervention. The participants reported instant benefits on confidence in their expertise in communicating with patients and their guardians. Additionally, perceived effects on the empathy and professionalism were reported. CONCLUSION: SBE, that is based upon adult and experiential learning theories, and developed after thorough consideration of the individual learners, and their experiences and learning environments, holds potential in enhancing communication skills among post-graduate dental students.